2005
DOI: 10.1073/pnas.0503366102
|View full text |Cite
|
Sign up to set email alerts
|

CD1d ligation on human monocytes directly signals rapid NF-κB activation and production of bioactive IL-12

Abstract: Natural killer T cells (NKT cells) expressing a semiinvariant CD1d-reactive T cell receptor (invariant NKT, iNKT) can be rapidly activated by monocytes or immature dendritic cells (iDCs) bearing aCD1d-presented glycolipid antigen and can in turn stimulate these myeloid cells to mature and produce IL-12. Previous studies have shown that iNKT-produced IFN␥ and CD40 ligand contribute to this dendritic cell maturation. This study demonstrates that CD1d ligation alone, in the absence of iNKT, could rapidly (within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 38 publications
3
104
0
Order By: Relevance
“…CD62L + NKT cells may be CD1d dependent [38]. It is also notable that our results do not completely rule out the possibility that CD1d blocking antibody may also trigger CD1d, and thus in some way promote inflammatory responses in the gut, especially through CD1d ligation on monocytes, which could enhance inflammation via induction of IL-12 [39]. However, previously published data indicate that CD1d cross-linking on epithelial cells leads rather to the production of barrier-enhancing and immunoregulatory cytokines [40].…”
Section: Discussionmentioning
confidence: 75%
“…CD62L + NKT cells may be CD1d dependent [38]. It is also notable that our results do not completely rule out the possibility that CD1d blocking antibody may also trigger CD1d, and thus in some way promote inflammatory responses in the gut, especially through CD1d ligation on monocytes, which could enhance inflammation via induction of IL-12 [39]. However, previously published data indicate that CD1d cross-linking on epithelial cells leads rather to the production of barrier-enhancing and immunoregulatory cytokines [40].…”
Section: Discussionmentioning
confidence: 75%
“…Similar to other restriction molecules, CD1d plays additional biological functions, including cell signaling. In fact, several studies demonstrated that CD1d ligation produces activating signals within human monocytes and intestinal intraepithelial cells (60,64). We demonstrated that the CD1d engagement alone produced a tolerogenic signal and induced IL-10 release by immature DCs.…”
Section: Discussionmentioning
confidence: 82%
“…However, we cannot exclude that, in vivo, iNKT cells with a strongly biased cytokine profile preferentially induce either protolerogenic or proinflammatory DC maturation. For example, high levels of IFN-g and IL-12 released by adjuvant iNKT cells could synergize with the maturation signal transmitted by iNKT cells through cell-cell contact and favor proinflammatory DC maturation (60).…”
Section: Discussionmentioning
confidence: 99%
“…Cd1d Ϫ/Ϫ C57BL/6 mice were previously reported to have an increased bacterial burden and joint inflammation after syringe infection with B. burgdorferi (30). However, T cells with more diverse TCRs also recognize CD1d; also, CD1d has been reported to have a signaling function that may be independent of T lymphocyte activity (33,34). In fact, in several experimental systems (35)(36)(37), analysis of Cd1d Ϫ/Ϫ and J␣18 Ϫ/Ϫ mice gave discordant results, suggesting either a role for CD1d-reactive T cells with more diverse TCRs or another function for CD1d besides antigen presentation.…”
Section: Discussionmentioning
confidence: 99%